Sustainable Waste Management and Social Capitals: The Experience from Landfill Community in Converting of Waste into Alternative Energy, in Kendari South East Sulawesi1 - Patta Hindi Asis; Ririn Syariani (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2016)
Management of waste into alternative energy that blends environmental capital and social capital has conducted by Independent Community Energy Landfill (TPA) Puwatu District Kendari South East Sulawesi. In this community, waste can be managed properly because the cooperation between by local Government and community and mutual trust among the members.The qualitative methods through case study approach this study is done that explore the data with study of literature/libraries, in-depth interviews, and focus group discussion (FGD) in TPA as partners in waste management activities into energy alternative.The result shows that waste management into alternative energy has run well because of the structure is supported by good relation between government as facilitator and the members of community. Social capitals such as personal interaction, trust and powerful networking in this community make the program of waste management sustainable that producing methane brings benefit to community as expected, and has become a pilot project.As recommendation, it is important to maintain the sustainability of waste management. Since the program leads to also maintaining social capitals of community; increasing skill of life, increasing leadership capability, finance skill and networking. Therefore the establishment of independent energy can be reached and continued as the way of people empowerment. Here the government should support by making regulation which assure its sustainability without influenced by leaders changing.